An Irish outbreak of New Delhi metallo-β-lactamase (NDM)-1 carbapenemase-producing Enterobacteriaceae: increasing but unrecognized prevalence. Issue 4 (December 2016) - O'Connor, C.; Cormican, M.; Boo, T.W.; McGrath, E.; Slevin, B.; O'Gorman, A.; Commane, M.; Mahony, S.; O'Donovan, E.; Powell, J.; Monahan, R.; Finnegan, C.; et al.
Summary: Background: Carbapenemase-producing Enterobacteriaceae (CPE) may cause healthcare-associated infections with high mortality rates. New Delhi metallo-β-lactamase-1 (NDM-1) is among the most recently discovered carbapenemases. Aim: To report the first outbreak of NDM-1 CPE in Ireland, including microbiological and epidemiological characteristics, and assessing the impact of infection prevention and control measures. Methods: This was a retrospective microbiological and epidemiological review. Cases were defined as patients with a CPE-positive culture. Contacts were designated as roommates or ward mates. Findings: This outbreak involved 10 patients with a median age of 71 years (range: 45–90), located in three separate but affiliated healthcare facilities. One patient was infected (the index case); the nine others were colonized. Nine NDM-1-producing Klebsiella pneumoniae, an NDM-1-producing Escherichia coli and a K. pneumoniae carbapenemase (KPC)-producing Enterobacter cloacae were detected between week 24, 2014 and week 37, 2014. Pulsed-field gel electrophoresis demonstrated similarity. NDM-1-positive isolates were meropenem resistant with minimum inhibitory concentrations (MICs) ranging from 12 to 32 μg/mL. All were tigecycline susceptible (MICs ≤1 μg/mL). One isolate was colistin resistant (MIC 4.0 μg/mL; mcr- 1 gene not detected). In 2015, four further NDM-1 isolates were detected. Conclusion: The successful management of this outbreak was achieved via the prompt implementation of enhanced infection prevention and control practices to prevent transmission. These patients did not have a history of travel outside of Ireland, but several had frequent hospitalizations in Ireland, raising concerns regarding the possibility of increasing but unrecognized prevalence of NDM-1 and potential decline in value of travel history as a marker of colonization risk.